Simulating intergrowth formation in zeolite crystals: impact on habit and functionality. (19th May 2022) - Trueman, Mollie; Akporiaye, Duncan; Anderson, Michael W.
Abstract : A kinetic Monte Carlo approach for modelling crystal growth, allowing simulation of crystal habit and surface fine structure in materials containing high levels of stacking faults. Abstract : A kinetic Monte-Carlo methodology is presented for simulating crystal growth in materials which contain stacking faults. By simulating a large number of potential growth and dissolution events, a representation of the crystal is generated at various stages throughout the crystallisation, allowing the effects of disorder on the evolution of crystal habit and nanoscale surface topography to be explored. As examples, simulations were performed on two intergrown zeolite materials – zeolite T and zeolite beta. In both zeolite T and zeolite beta, simulations demonstrate how an intergrown structure leads to a characteristic roughening of certain crystal facets. In zeolite beta, this is accompanied by the development of internal defects which shows a non-homogeneous distribution. Results of simulations are validated by direct comparison to experimental scanning electron microscopy, atomic force microscopy and X-ray diffraction data. All simulations are performed using the CrystalGrower software package with modifications to account for disorder and should be generally applicable to all classes of crystals.